Determinan Ketahanan Pemberian ASI Eksklusif di Provinsi NTT Tahun 2024 - Muhammad Suprapto (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
Breastfeeding is one of the investments that a country can make to ensure a smarter and better population. Longer duration of breastfeeding can increase intelligence levels which indirectly impact the success of a country's economic strength which has major implications for the future prosperity of a nation. Breastfeeding for the first 6 months of life no other liquids or solid as Exclusive Breastfeeding. The percentage for the first 6 months of life who received Exclusive Breastfeeding in NTT Province in 2021-2024 tended to decline. In addition, the achievement of exclusive breastfeeding in 2024 has not reached the government's target (80 percent) as stated in PP No. 72 of 2021 concerning the Acceleration of Stunting Reduction. This condition actually occurs along with the improvement in the condition of health facility infrastructure and the increase in the number of health human resources. So, it’s necessary to review what variables have a role in the exclusive breastfeeding sustainability in order to find out the overview of exclusive breastfeeding and the best model in the analysis of exclusive breastfeeding sustainability in NTT Province in 2024. This study is based on National Socioeconomic Survey 2024 and using the Survival Analysis method. The results of the study showed that the best model formed was the log-logistic model with the variables initiation of breastfeeding (IMD), economic status, area of ​​residence, and family planning (KB) which had a significant effect (α = 5 percent) on the exclusive breastfeeding sustainability in NTT Province in 2024.